Surfactant Protein Type-A in Diagnosis of Drowning Cases (Iraqi Journal of Medical Sciences, 2020)
Background: Drowning is a main universal community health problem. In medico-legal practice, the autopsy diagnosis of drowning presents one of the major problems especially when there is delay in recovering the victim from water.Objective: To gather the autopsy findings with the serology test "Surfactant-associated protein A" (SP-A) procedures to reach more accurate diagnosis of drowning and to clarify the significance of serology test (SP-A) procedures.Methods: This study was performed at Medico-legal Directorate (MLD) in Baghdad for (12) months within the period from 1/1/2018 to 31/12/2018. Full proper autopsy including external and internal examination of the body for all cases was performed, after obtaining complete medico-legal history, in addition to serology test (SP-A) procedures to determine the cause of the death as due to drowning.Results: The study included (60) cases, (52) males and (8) females with their ages ranged between (15-44 years old) for male, while ages ranged between (1-44 years old) for females. Drowning was the cause of death in all cases. The most important result of this study is that the serum SP-A concentration showed increment alongside with period that had been passed since the event of drowning. The highest value was (1042.167 ng /L) after 48 hours from the event.Conclusion: The concentration of SP-A increases with increasing duration of immersion in water and an important marker in the diagnosis of drowning together with the autopsy findings.Keywords: Medico-legal study, SP-A, drowningCitation: Hussein HN, Hashim NG, Abdulla MA. Surfactant Protein Type-A in diagnosis of drowning cases. Iraqi JMS. 2020; 18(1): 21-28. doi: 10.22578/IJMS.18.1.4
Keywords: Medicolegal study; SPA; drowning